The end(s) of inclusion: ungrounding globalization and 'the migrant' in dialogue with hospitality. Issue 5 (3rd September 2021) - Kirchgasler, Christopher
ABSTRACT: This article reassesses globalization in light of research, policy, and reforms directed towards 'the migrant' during times of crisis. In dialogue with Derrida's discussion of hospitality, the article questions the grounds that figure 'the migrant' as a metonym for globalization's dangers – as excess mobility menacing the foundational sovereignty of nation-states. With Sweden as a point of reference, the article interrelates three seemingly distinct techniques for evaluating notions of arrival – data visualizations comparing 'the migrant' against those 'without immigrant background', curriculum and pedagogy seeking to integrate and include according to psychologized norms and values, and critical qualitative research representing migrant voice. At issue in each is how the gesture of hospitality seeks to render arrival calculable, establishing the authority and beneficence of the host and leaving 'the migrant' indefinitely at the threshold of (non)belonging. Efforts to represent the migrant through notions of experience and 'voice' risk naturalizing hospitality's asymmetries and exclusions, while impeding reflexivity toward the conditions upon which hospitality remains tenuously granted.